1999
DOI: 10.1016/s0194-5998(99)70269-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effectiveness of Levofloxacin and Amoxicillin‐Clavulanate for the Treatment of Acute Sinusitis in Adults

Abstract: In this comparative trial, outpatients with acute sinusitis were randomly assigned to receive levofloxacin (500 mg orally once daily) or amoxicillin-clavulanate (500/125 mg orally 3 times daily) for 10 to 14 days. The success rates (cured and improved) 2 to 5 days after the end of treatment were 88.4% for the 267 clinically evaluable patients who received levofloxacin and 87.3% for the 268 clinically evaluable patients who received amoxicillin-clavulanate. Drug-related adverse events occurred in a smaller perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 22 publications
3
26
0
3
Order By: Relevance
“…Clarithromycin and amoxicillinclavulanate also showed similar results. [11][12][13] In a study conducted by Wald et al to compare amoxicillin and amoxicillin-clavulanate with placebo amongst 93 children in a 10 day trial. They found that the cure rate amongst children who received antibiotics was 67%, whereas only 43% of those receiving placebo showed resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Clarithromycin and amoxicillinclavulanate also showed similar results. [11][12][13] In a study conducted by Wald et al to compare amoxicillin and amoxicillin-clavulanate with placebo amongst 93 children in a 10 day trial. They found that the cure rate amongst children who received antibiotics was 67%, whereas only 43% of those receiving placebo showed resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Two additional trials eligible for inclusion were detected after a secondary search on the Scopus database, but no additional trials were identified in the Cochrane Central Register of Controlled Trials. A total of 11 trials [21][22][23][24][25][26][27][28][29][30][31] were included in the meta-analysis ( Figure 1). The 2 reviewers independently reached the same conclusions regarding studies to be included.…”
Section: Selected Trialsmentioning
confidence: 99%
“…In addition to the treatments being compared in these studies, adjunctive medications for symptomatic relief, mostly decongestants, antihistamines and analgesics, were permitted in 8 of the trials. 22,[24][25][26][27][28][29][30] Two of these trials reported the percentage of patients using such medications: 76% in one study 28 and 83.5% in the other.…”
Section: Characteristics Of the Selected Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Furthermore, gastrointestinal disorders are the most common adverse reactions observed with use of levofloxacin (5.1%). 8,9 These reactions include diarrhea, nausea, flatulence, abdominal pain, dyspepsia, taste perversion, and vomiting. Chronic medical conditions such as chronic renal failure, antihypertensive medications such as valsartan, and gout treatments such as allopurinol are known to cause taste disturbances.…”
Section: Mirtazapine Therapy For Dysgeusia In An Elderly Patientmentioning
confidence: 99%